Expression of β-catenin and c-myc during human common bile duct development: a possible role in the morphogenesis of the common bile duct - Guo,W.L. (2014)
β-catenin and c-myc play important roles in the development of tissues and organs. However, little is known about their expression patterns during the development of the human common bile duct. Immunohistochemistry was used to detect β-catenin and c-myc expression in common bile duct samples from postmortem tissues of 14 premature infants and 6 spontaneously aborted fetuses. The expression of β-catenin and c-myc was also analyzed by Western blot. The samples were divided into four groups based on the stage of human fetal development: 12, 13-27, 28-37, and >37 weeks. The Image-Pro Plus v. 6.0 image analysis software was used to calculate the mean qualifying score (MQS). At fetal stages 12, 13-27, 28-37, and >37 weeks, MQS of β-catenin were 612.52±262.13, 818.38±311.73, 706.33±157.19, and 350.69±110.19, respectively. There was a significant difference in MQS among the four groups (ANOVA, P=0.0155) and between the scores at >37 and 13-27 weeks (Student-Newman-Keuls, P<0.05). At fetal stages 12, 13-27, 28-37, and >37 weeks, the MQS of c-myc were 1376.64±330.04, 1224.18±171.66, 1270.24±320.75, and 741.04±219.19, respectively. There was a significant difference in MQS among the four groups (ANOVA, P=0.0087) and between the scores at >37 and 12 weeks, >37 and 13-27 weeks, and >37 and 28-37 weeks (all P<0.05, Student-Newman-Keuls). Western blots showed that β-catenin and c-myc expression were significantly higher in fetal than in postnatal control duct tissue (P<0.05). c-myc and β-catenin are involved in the normal development of the human common bile duct.